Motivation in the metaverse: A dual-process approach to consumer choices in a virtual reality supermarket - Saffari, Farzad; Kakaria, Shobhit; Bigné, Enrique; Bruni, Luis E.; Zarei, Sahar; Ramsøy, Thomas Z. (Frontiers in Neuroscience, 2023)
Consumer decision-making processes involve a complex interrelation between perception, emotion, and cognition. Despite a vast and diverse literature, little effort has been invested in investigating the neural mechanism behind such processes. In the present work, our interest was to investigate whether asymmetrical activation of the frontal lobe of the brain could help to characterize consumer’s choices. To obtain stronger experimental control, we devised an experiment in a virtual reality retail store, while simultaneously recording participant brain responses using electroencephalogram (EEG). During the virtual store test, participants completed two tasks; first, to choose items from a predefined shopping list, a phase we termed as “planned purchase”. Second, subjects were instructed that they could also choose products that were not on the list, which we labelled as “unplanned purchase”. We assumed that the planned purchases were associated with a stronger cognitive engagement, and the second task was more reliant on immediate emotional responses. By analysing the EEG data based on frontal asymmetry measures, we find that frontal asymmetry in the gamma band reflected the distinction between planned and unplanned decisions, where unplanned purchases were accompanied by stronger asymmetry deflections (relative frontal left activity was higher). In addition, frontal asymmetry in the alpha, beta, and gamma ranges illustrate clear differences between choices and no-choices periods during the shopping tasks. These results are discussed in light of the distinction between planned and unplanned purchase in consumer situations, how this is reflected in the relative cognitive and emotional brain responses, and more generally how this can influence research in the emerging area of virtual and augmented shopping.